The consequences of malnutrition following discharge from rehabilitation to the community: a systematic review of current evidence in older adults. Issue 2 (30th November 2013) - Marshall, S.; Bauer, J.; Isenring, E.
Abstract Background The prevalence of malnutrition in the rehabilitation setting is estimated to be 30–50%, with older adults at higher nutritional risk. Malnutrition also exists in the community setting, where 10–30% of adults are malnourished; however, the relationship between the two settings has been little explored. The present study aimed to determine the association between malnutrition in older adults admitted for rehabilitation and nutrition status, functional status, quality of life, institutionalisation, acute care admissions and mortality once discharged to the community. Methods Six electronic databases were searched for relevant publications (1990–2013) using controlled vocabulary. Longitudinal papers were included in which older adults (≥65 years) were admitted for rehabilitation if nutrition assessment was performed during admission with relevant outcomes measured following discharge to the community. Results Five observational studies were eligible for review which had similar populations. The five reviews comprised 1020 participants in total and, once discharged, follow‐up ranged from immediate to 26 months. Malnutrition during rehabilitation was negatively associated with physical function and quality of life, and positively associated with risk of institutionalisation, hospitalisation and mortality. Although these studies were of high quality and strength, the overall contribution to the evidence is limited as a result of the small number of heterogenic studies. No intervention studies were identified. Conclusions Malnutrition in older adults admitted for rehabilitation has a negative effect on functional recovery and quality of life following discharge to the community. This review highlights an evidence gap along the continuum of care for malnourished older adults, where further observational and intervention research is needed following discharge from rehabilitation to the community.